Incidencia en el incremento de peso y consumo de alimento de litopenaeus vannamei con tres tratamientos de probiótico en el alimento y en el medio - Granillo Rosales, Rodrigo Javier (2007)
The present work one carries out in the unit of shrimp production Puna one of property of the Family Valarezo. The pools used for the present investigation were: Pool 16 (5 have), pool 17 (5 have) and pool 27 (2.5 have). The outlined objectives were. 1. to determine the incidence of the probiotic treatments on the increment of weight. 2. to establish the relationship on the increment in the food consumption in the probiotic treatments. The Statistical Analysis for the weekly increment of weight and of the one balanced it indicates that there is not significant difference for the three treatments. The weekly increment of weight had a better result in treatment three, followed by the treatment one and finally the treatment two. The weekly increment of balanced food had a better incidence in the treatment one, followed by the treatment two and finally the treatment three.